Analisis kebijakan manajemen risiko cicilan rumah pada bank syariah indonesia (bsi) - muqaffa, dzaki (Maliki Interdisciplinary Journal, 2025)
This study discusses the risk management policies in home financing (KPR) at Bank Syariah Indonesia (BSI). In practice, KPR financing faces various risks such as credit risk, sharia compliance risk, market risk, liquidity risk, operational risk, legal risk, and reputational risk. These risks can threaten the stability and sustainability of financial institutions if not properly managed. Therefore, the implementation of effective and structured risk management is essential. Bank Syariah Indonesia applies risk mitigation strategies through a systematic approach, including the 5C principle in financing analysis, compliance with DSN-MUI fatwas, balanced asset and liability management, and internal system strengthening. The study shows that comprehensive risk management can help the bank minimize potential losses and maintain public trust in sharia financial institutions.